PROFESSIONAL IMAGE OF A NURSE AS A FACTOR OF INCREASING THE EFFICIENCY OF HEALTH CARE - Светличная, Татьяна Геннадьевна; Плаксин, Владимир Александрович; Петрухина, Виктория Витальевна (Medicine in Kuzbass, 2022)
In the modern world, the idea of the image of a medical worker is changing. The analysis of the images of heroes presented by the authors of literary and film productions demonstrates a change in the foundations of both the choice of profession and the personality of women who come to it. A compassionate and experienced nurse is replaced by a strong, self-confident professional. There remain the dedication necessary in the profession, the desire for self-improvement, initiative, observation, logical behavior. Negative qualities are also noted, manifested in mechanicality, stereotyping, stereotype of work, lack of consideration of psychological characteristics and indifference to the patient.
Keywords: nurse; professional image; public consciousness; health care efficiency